Older people’s travel and mobility needs: a reflection of a hierarchical model 10 years on - Charles Musselwhite (Quality in Ageing and Older Adults, 2018)
In 2010 we published a model of older people’s travel and mobility needs in the Quality of Ageing and Older Adults journal (Musselwhite and Haddad, 2010). The model comprises three levels, practical (the need to get from A to B as quickly, cheaply and efficiently as possible), psychosocial (the need for independence, control and status) and aesthetic needs (the need for travel for its own sake), all which need to be fulfilled to achieve wellbeing and quality of life. Since then, the model has been translated into different languages and been cited 119 times across different formats.Design/methodology/approach: Using 10 years of analysing feedback that includes articles that cited the model, discussions with academics, policymakers and practitioners as well as from older people themselves, this paper reflects on the original model.Findings: Five key themes are generated from the re-examination: (1) the validity of the model; (2) the utility and usefulness of needs in understanding travel behaviour and turning them into policy or practice; (3) application of the model to different contexts; (4) understanding the relationship between travel needs and health and wellbeing; and (5) fitting the model to future changes in transport and social policy.Research limitations/implications:Practical implications:Originality/value: This reflection on this well cited and well used model allows a re-adjustment of the model, updating it to be used in conjunction with policy and practice, especially highlighting the need to further distinguish mobility for aesthetic needs.